THE FACTOR OF PRIMIPARA AGE ON THE TAKING IN PHASE PROCESS IN THE PUERPERIUM PERIOD: PENGARUH USIA PRIMIPARA TERHADAP PROSES FASE TAKING IN PADA MASA PUERPERIUM - Wenny Rahmawati (LPPM Widyagama Husada Malang, 2023)
The puerperium is a period of physiological and psychological changes in the mother. During the puerperium, about 85% of women experience psychological disorders, including tension, panic, anxiety, confusion and fear. This disorder affects the success of passing through the psychological phase, namelyfase taking in or dependency phase. This phase lasts 1-2 days where the mother is still focusing on herself. Age is one of the factors that influence the psychological readiness of the mother in dealing with itphase taking in This. The aim of the study was to determine the effect of ageprimiparous on sustainabilityfase taking in on timepuerperium. The research was conducted in Wirotaman Village, Ampelgading District, Malang Regency. This study uses a correlational analytic design with an approachcross sectional. This research was conducted by interviewing and observing 30 primiparas. Subjects were taken from the population by means of total sampling. The results of the study showed that there was a relationship between primiparous age andfase taking in. Based on these results it was concluded that the more mature the age, the fasterfase taking in primipara (p value<0.05). Therefore, it is expected for young women to marry or give birth at the ideal age, which is between 20-30 years. Because with the ideal age, the process of pregnancy, childbirth and postpartum can run normally.